Power and energy management optimization for marine transportation electrification - Hein, Kyaw (Nanyang Technological University, 2022)
With the prediction of greater reliance on marine transportation for social and economic growth in the future, the development of energy-efficient and environmentally friendly design and operation of the ships are becoming the main focus of research and industry. Furthermore, due to the excessive emission from marine vessels, the International Maritime Organization (IMO) and regulatory authorities impose stringent rules and regulations to limit the overall emission. Over the past few years, the concept of more electrification, renewable energy resources, electrical energy storage integration, and energy optimization in land-based microgrid systems have proven to improve operational efficiency and reliability. Thus, there is an attempt to adapt existing solutions from the land-based microgrid to a more electric ship power system (mobile isolated microgrids). However, unlike its land-based counterparts, deriving power and energy management strategies to improve operational efficiency is a complex and unique problem for a marine vessel. It has to address multiple aspects of ship design and operation to establish a realistic operation scenario for a marine vessel. Furthermore, propulsion architecture selection, task-sequence planning, path selection, voyage scheduling, energy network coordination, short-term maintenance schedules, uncertainty management, and unique load management are additional dimensions of the mobile ship power system that introduce control, power, and energy dispatch complexity.